Progression of disease in ocular cicatricial pemphigoid. Issue 4 (April 1996) - Elder, M J; Bernauer, W; Leonard, J; Dart, J K
Abstract : BACKGROUND: Ocular cicatricial pemphigoid (OCP) is a sight threatening autoimmune disease that can lead to severe conjunctival cicatrisation and keratopathy. It has a variable course and little is known about the factors that determine disease progression. This study analysed the factors that have prognostic significance regarding disease outcome, progression, and keratopathy. METHODS: Sixty six patients with OCP were monitored prospectively at Moorfields Eye Hospital. The influence of ocular features, the systemic disease, and the management were analysed to identify factors that influence the outcomes and disease progression. RESULTS: The mean age at presentation was 67 years; 56% were men. The binocular visual acuities were 6/24 or worse in 25%. Extensive cicatrisation at presentation was common but correlated only weakly with the visual prognosis. Systemic manifestations included lesions of the mouth in 44%, pharynx in 30%, oesophagus in 27%, nose/sinus in 18%, and skin in 17%. There was no association between the ocular and systemic manifestations. Persistent corneal epithelial defects and limbitis occurred in 18% and 32%, respectively, and both were associated with a worse visual prognosis. Systemic immunosuppression was ultimately prescribed in 74%, mainly in patients with advanced stages of conjunctival cicatrisation. Of patients with more than 24 months follow up, progression of cicatrisation occurred in 35% of eyes (16/46) all but one of which were associated with episodes of conjunctival inflammation. CONCLUSIONS: Persistent epithelial defects, limbal inflammation, and ongoing conjunctival inflammation are important factors that lead to keratopathy and visual handicap. These require aggressive management, often with systemic immunosuppressive treatment. Close follow up is required in cases with extensive cicatrisation.